PENGARUH ONLINE CUSTOMER REVIEW DAN RATING TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PRODUK SCARLETT WHITENING - Virawanti, Adinda Cantica; Sudarwanto, Tri (Jurnal Pendidikan Tata Niaga (JPTN), 2023)
This study aims to determine how influential Online Customer Review and Online Customer Rating are partially and simultaneously on Purchasing Decisions. This study uses the type of Explanatory Research using a quantitative approach. The population taken in this study are consumers who use scarlett whitening products in the Surabaya area using a sampling technique, namely Purposive Sampling and using the Lemeshow et al,. formula, with a minum sample size of 100 people. Respondent data was taken via google form and measured using a linkert scale and processed with SPSS version 25 using multiple linier regression analysis methods. The results of this study indicate that there is a positive influence between the relationship between Online Customer Review on purchasing decisions and a positive influence between Online Customer Rating on purchasing decisions. The results of this study ecplain that Online Customer Review and Rating on purchasing decisions simultaneously have a positive influence. Keywords: Online Customer Review, Online Customer Rating, Purchasing Decision.